2003
DOI: 10.1119/1.1507791
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with the magnetism of conducting loops: Historical instruments, experimental replications, and productive confusions

Abstract: This study investigates nineteenth century laboratory work on electromagnetism through historical accounts and experimental replications. Oersted found that when a magnetic needle was placed in varying positions around a conducting wire, its orientation changed: in moving from a spot above the wire to one below, its sense inverted. This behavior was confusing and provocative. Early experimenters such as Johann Schweigger, Johann Poggendorff, and James Cumming engaged it by bending wire into loops. These loops,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
8
0
4
Order By: Relevance
“…For example, Dunbar & Fugelsang (2005), in an "in vivo" study of scientific laboratories, found a high proportion of discussion centered on unexpected results, with a good part of the work done by scientists devoted to understanding such "counterintuitive" results. Similarly, in an analysis of the historical development of induction coils, Cavicchi (2003) noted that utter confusions played an important role in the search for order underlying the complex behavior of various configurations of coil, magnet, materials, and so on. Tweney, Mears, & Spitzmüller (2005) found similar productive confusions in the notebooks of Michael Faraday.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Dunbar & Fugelsang (2005), in an "in vivo" study of scientific laboratories, found a high proportion of discussion centered on unexpected results, with a good part of the work done by scientists devoted to understanding such "counterintuitive" results. Similarly, in an analysis of the historical development of induction coils, Cavicchi (2003) noted that utter confusions played an important role in the search for order underlying the complex behavior of various configurations of coil, magnet, materials, and so on. Tweney, Mears, & Spitzmüller (2005) found similar productive confusions in the notebooks of Michael Faraday.…”
Section: Discussionmentioning
confidence: 97%
“…But what good is clarity and certainty about stories that are false, at best very limited? Cavicchi (2003Cavicchi ( , 2009) and Crawford (1993) even argue quite plausibly that confusion has a positive pedagogical role to play.…”
Section: Can Complementary Experiments Help Science Education?mentioning
confidence: 93%
“…Douglas Allchin and his colleagues incorporated historical experiments into an innovative interdisciplinary science course for nonmajors (Allchin et al 1999), and Allchin has since then launched a larger initiative to train and support science teachers in the use of history of science, including experimentation. 3 Elizabeth Cavicchi (2003Cavicchi ( , 2006Cavicchi ( , 2008Cavicchi ( , 2009) has explored the nature of science learning through intensive individual work with students in a variety of historical experiments; Cavicchi's work has great affinity to Elspeth Crawford's (1993) practice of using the history of science including experiments to develop independent thinking in students. The various and coordinated efforts by scholars in the European Group on History of Physics in Education have included experimental work (see Bevilacqua andGiannetto 1998, p. 1022).…”
mentioning
confidence: 98%
“…Estes instrumentos ficaram conhecidos como multiplicadores e, de um modo geral, envolviam várias voltas de um fio de cobre formando espiras, com as extremidades livres para conectar à bateria. As voltas podiam ser sobrepostas ou paralelas, verticais ou horizontais, e no seu centro ficava a bússola 7 [17,18]. Para estes instrumentos, diferentes variáveis influenciavam no resultado final, e muitas ainda não eram conhecidas e, portanto, não era possível saber como afetavam a intensidade e a direção do magnetismo ao redor do fio.…”
Section: O Ano De 1820unclassified